PENGEMBANGAN PERANGKAT PEMBELAJARAN MENGGUNAKAN MODEL PBL DENGAN SA-TPACK PADA MATERI IPA SIKLUS AIR KELAS V DI SDN BULUSARI 3 - Eva Dwi Agustina; Kharisma Eka Putri; Alfi Laila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article aims to develop learning tools using the PBL model with SA-TPACK on the water cycle science material for fifth-grade students of SDN Bulusari 3. The background of this study is the problem that fifth-grade students of SDN Bulusari 3 still have difficulty in understanding the water cycle material and students often get bored during the learning process. The method used is Research and Development (R&D) with the ADDIE development model which includes the stages: Analysis, Design, Development, Implementation, and Evaluation. The research instruments are interviews, validation by validator 1 and validator 2, response questionnaires, and learning outcome tests. Data analysis techniques include qualitative and quantitative analysis. The validation results show that the learning tools using the PBL model with SA-TPACK meet the criteria of Very Valid with validator 1 obtaining results of 93% and validator 2 obtaining results of 97%. The practicality of the learning tools based on the teacher response questionnaire obtained results of 92% and student responses of 94%, included in the Very Practical category. The effectiveness test shows that 89% of students achieved learning mastery with post-test scores above the KKM, included in the Very Effective category. The learning toolkit using the PBL model with SA-TPACK was declared valid, practical, and effective for use in science teaching, particularly on the air cycle. This learning toolkit can be an alternative solution to improve elementary school students' understanding and learning outcomes. Penelitian ini bertujuan untuk mengembangkan perangkat pembelajaran menggunakan model PBL dengan SA-TPACK pada materi IPA siklus air siswa kelas V SDN Bulusari 3. Latar belakang penelitian ini adalah permasalahan bahwa siswa kelas V SDN Bulusari 3 masih mengalami kesulitan dalam memahami materi siklus air dan siswa sering bosan selama pembelajaran berlangsung. Metode yang digunakan adalah Research and Development (R&D) dengan model pengembangan ADDIE yang meliputi tahapan: Analysis, Design, Development, Implementation, dan Evaluation. Instrumen penelitian berupa wawancara, validasi oleh validator 1 dan validator 2, angket respon, serta tes hasil belajar. Teknik analisis data meliputi analisis kualitatif dan kuantitatif. Hasil validasi menunjukkan bahwa perangkat pembelajaran menggunakan model PBL dengan SA-TPACK memenuhi kriteria Sangat Valid dengan diperoleh hasil validator 1 93% dan validator 2 diperoleh hasil 97%. Kepraktisan perangkat pembelajaran berdasarkan angket respon guru memperoleh hasil 92% dan respon siswa 94%, termasuk dalam kategori Sangat Praktis. Uji keefektifan menunjukkan bahwa diperoleh 89% siswa mencapai ketuntasan belajar dengan nilai post-test di atas KKM, termasuk dalam kategori Sangat Efektif. Perangkat pembelajaran menggunakan model PBL dengan SA-TPACK dinyatakan valid, praktis, dan efektif untuk digunakan dalam pembelajaran IPA, khususnya pada materi siklus air. Perangkat pembelajaran ini dapat menjadi alternatif solusi dalam meningkatkan pemahaman dan hasil belajar siswa sekolah dasar.